High-performance low-temperature lithium battery cathode material, preparation method and application thereof
Patent Information
- Application Number
- CN202611162795.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-09-29
AI Technical Summary
然而,将冷冻干燥技术与等离子体辅助烧结技术相结合,用于在单晶NCM表面构建具有纳米多孔结构的快离子导体/电子导体复合包覆层,以系统性地提升低温电化学性能,在现有文献和专利中尚未见报道
[0028]通过本发明的技术方案,可实现以下技术效果:本发明通过将冷冻干燥技术与射频等离子体辅助烧结技术相结合,采用水或乙醇等绿色溶剂配制前驱体浆料,先经快速冷冻与真空冷冻干燥在单晶镍钴锰酸锂基体表面原位构建连续贯通的纳米多孔复合包覆层前驱体,再通过低温等离子体烧结实现快离子导体的结晶化、电子导体的转化以及包覆层与基体间的强界面化学键合,既避免传统高温烧结工艺导致的基体晶粒长大、结构损伤和包覆层致密化缺陷,又使复合包覆层同时具备丰富的锂离子快速传输通道与优异的电子导电能力,显著降低低温下的界面电荷转移阻抗,提升正极材料的低温放电容量、倍率性能和循环稳定性。
Smart Images

Figure CN122843347A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery cathode material technology, and in particular to a high-performance low-temperature lithium battery cathode material, its preparation method, and its application. Background Technology
[0002] With the increasing demands on lithium-ion battery performance from new energy vehicles and energy storage systems, cathode materials, as key components determining battery energy density and low-temperature performance, have received widespread attention. Nickel-cobalt-manganese ternary cathode materials (LiNi...) x Co y Mn 1-x-y O2 (NCM) has become the mainstream choice for power batteries due to its high specific capacity and relatively low cost. Among them, monocrystalline NCM has shown significant advantages in structural stability and cycle life because it eliminates the grain boundaries of polycrystalline materials.
[0003] However, the application of single-crystal NCM cathode materials in low-temperature environments still faces severe challenges. At low temperatures, the diffusion rate of lithium ions in the bulk phase and interface of the electrode material decreases significantly, and the electrolyte viscosity increases, leading to a sharp increase in charge transfer impedance. This manifests as a significant decrease in discharge capacity, a drop in discharge plateau, and a deterioration in rate performance. Especially in extremely cold environments below -20°C, the capacity retention of conventional single-crystal NCM materials is typically less than 60% of that at room temperature, making it difficult to meet the application requirements of electric vehicles and special equipment in high-altitude and cold regions.
[0004] Surface coating modification is a common method to improve the low-temperature performance of single-crystal NCM. Coating with fast ion conductors (such as LATP, LLZO, etc.) can improve the interfacial lithium-ion transport rate, while coating with electronic conductors (such as carbon materials, conductive polymers, etc.) can improve electronic conductivity.
[0005] In recent years, freeze-drying technology has demonstrated unique advantages in the field of materials preparation. By rapidly freezing and removing solvents through vacuum sublimation, abundant nanoporous structures can be constructed in situ within materials, providing rapid channels for ion transport. Plasma-assisted sintering (PAS) utilizes high-energy active particles to achieve crystallization and interfacial bonding of materials at lower temperatures, effectively avoiding damage to the matrix structure caused by high temperatures. However, the combination of freeze-drying and PAS for constructing a fast ion conductor / electron conductor composite coating with a nanoporous structure on the surface of single-crystal NCM to systematically improve low-temperature electrochemical performance has not yet been reported in existing literature and patents.
[0006] The information disclosed in this background section is intended only to enhance the understanding of the general background of this disclosure and should not be construed as an admission or in any way implying that the information constitutes prior art known to those skilled in the art. Summary of the Invention
[0007] This invention provides a high-performance low-temperature lithium battery cathode material, its preparation method, and its application. A fast ion conductor / electron conductor composite coating precursor with a nanoporous structure is constructed on the surface of single-crystal lithium nickel cobalt manganese oxide using freeze-drying technology. Then, plasma-assisted sintering technology is used to achieve crystallization and interfacial bonding of the coating at low temperature. While avoiding damage to the matrix structure at high temperature, a porous composite coating with abundant lithium-ion fast transport channels and strong interfacial bonding is formed, achieving high discharge capacity and excellent cycle stability of the material in a low-temperature environment.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of this invention provides a method for preparing a high-performance low-temperature lithium battery cathode material, the method comprising: S1 disperses the single-crystal lithium nickel cobalt manganese oxide matrix powder, fast ion conductor precursor, electronic conductor precursor and binder in a solvent and mixes them evenly to obtain a precursor slurry. This step enables the fast ion conductor precursor, electronic conductor precursor and binder to be uniformly distributed on the surface of the single-crystal lithium nickel cobalt manganese oxide matrix particles at the molecular or nanoscale, providing a material basis for the subsequent formation of a composite coating layer with uniform thickness and composition on the matrix surface. S2 involves rapidly freezing the precursor slurry at -50℃ to -196℃, followed by freeze-drying under vacuum for 24 to 48 hours to obtain a composite coating precursor with a nanoporous structure. This step, through rapid freezing, enables the solvent to solidify instantly, inhibiting the agglomeration, sedimentation, and phase separation of precursor particles, and maintaining the uniform distribution of each component on the surface of the single-crystal lithium nickel cobalt manganese oxide matrix. Subsequently, vacuum freeze-drying removes the frozen solvent directly by sublimation, avoiding particle agglomeration and structural collapse caused by solvent surface tension during traditional heating and drying processes. This allows for the in-situ construction of a composite coating precursor with a continuous, interconnected nanoporous structure on the surface of the single-crystal lithium nickel cobalt manganese oxide matrix, providing abundant diffusion channels for the rapid transport of lithium ions at low temperatures. S3 places the composite coating precursor in a plasma treatment device and performs assisted sintering treatment using radio frequency plasma under an inert or reducing atmosphere. The radio frequency power is 200~500W, the treatment time is 10~60 minutes, and the atmosphere pressure is 10~100Pa. This step uses radio frequency plasma-assisted sintering technology, which utilizes the bombardment and energy transfer effect of high-energy active particles in the plasma. Under a relatively low power of 200~500W and an atmosphere pressure of 10~100Pa, the low-temperature crystallization of the fast ion conductor precursor and the preliminary transformation of the electronic conductor precursor can be achieved in just 10~60 minutes. A strong interfacial chemical bond is formed between the composite coating and the single-crystal nickel cobalt manganese oxide matrix, avoiding the problems of matrix grain growth, structural damage, and coating densification caused by traditional high-temperature sintering processes. This ensures the structural stability of the matrix and gives the composite coating excellent ionic conductivity and electronic conductivity at the same time. S4 involves cooling, grinding, and sieving the product after assisted sintering to obtain a high-performance low-temperature lithium battery cathode material. This step involves naturally cooling the plasma-treated product to room temperature under an inert atmosphere to prevent the material from reacting with moisture and oxygen in the air at high temperatures, thus preventing the introduction of impurities. Subsequently, grinding and sieving can break up the slightly agglomerated particles generated during sintering, resulting in cathode material powder with uniform particle size distribution and good dispersibility. This improves the uniformity of slurry coating and the consistency of the electrode sheet in the subsequent battery electrode preparation process.
[0009] The preparation method of this invention combines freeze-drying technology with radio frequency plasma-assisted sintering technology. A precursor slurry is prepared using green solvents such as water or ethanol. First, a continuous, interconnected nanoporous composite coating precursor is constructed in situ on the surface of a single-crystal lithium nickel cobalt manganese oxide substrate through rapid freezing and vacuum freeze-drying. Then, low-temperature plasma sintering is used to achieve crystallization of fast-ion conductors, conversion of electronic conductors, and strong interfacial chemical bonding between the coating and the substrate. This avoids the defects of substrate grain growth, structural damage, and coating densification caused by traditional high-temperature sintering processes. Furthermore, the composite coating possesses abundant lithium-ion fast transport channels and excellent electronic conductivity, significantly reducing interfacial charge transfer impedance at low temperatures and improving the low-temperature discharge capacity, rate performance, and cycle stability of the cathode material.
[0010] Furthermore, the chemical formula of the single-crystal lithium nickel cobalt manganese oxide matrix powder is LiNi x Co y Mn 1-x-y O2, where 0.3≤x≤0.9, 0.05≤y≤0.3.
[0011] More specifically, the above range can effectively balance the structural stability and low-temperature electrochemical performance of the material while ensuring that the cathode material has a high specific capacity. A higher nickel content can improve the theoretical specific capacity of the material, an appropriate amount of cobalt can stabilize the layered structure of the material and improve electronic conductivity, while manganese can reduce costs and improve the thermal stability of the material, thus avoiding problems such as structural collapse, shortened cycle life or deterioration of low-temperature performance caused by excessive content of a single element.
[0012] Furthermore, the fast ion conductor precursor is selected from salts or alkoxides containing at least two elements from Li, Al, Ti, La, Zr, Ge, and P, and is used to form at least one of the fast ion conductors LATP (lithium aluminum titanium phosphate), LLZO (lithium lanthanum zirconium oxide), LLTO (lithium lanthanum titanate), and LAGP (lithium aluminum germanium phosphate).
[0013] More specifically, the aforementioned salts or alkoxide precursors containing Li, Al, Ti, La, Zr, Ge, and P elements have good solubility and dispersibility, and can be uniformly distributed on the substrate surface and transformed into fast ion conductors such as LATP, LLZO, LLTO, or LAGP during subsequent low-temperature sintering. These fast ion conductors have high lithium-ion conductivity and excellent chemical stability, and can construct a continuous lithium-ion transport network in the coating layer, significantly reducing the lithium-ion migration resistance at the interface at low temperatures. At the same time, they can effectively prevent direct contact between the electrolyte and the substrate, and suppress the occurrence of side reactions.
[0014] Furthermore, the electronic conductor precursor is selected from at least one of graphene oxide, carbon nanotubes, MXene nanosheets, and conductive polymer monomers; The conductive polymer monomers include at least one of aniline, pyrrole, and thiophene.
[0015] More specifically, the aforementioned electronic conductor precursors all possess excellent electronic conductivity and nanoscale structural features, enabling them to form a continuous and uniform electronic conductivity network on the substrate surface. Among them, two-dimensional layered graphene oxide and MXene nanosheets can form an interlaced composite structure with fast ion conductors, providing both ion and electron transport channels. One-dimensional carbon nanotubes can construct long-range conductive pathways, while conductive polymer monomers can achieve uniform coating of substrate particles through in-situ polymerization, further enhancing the electronic conductivity of the composite coating layer.
[0016] Furthermore, a post-processing step is included between S3 and S4: When the electronic conductor precursor is graphene oxide or carbon nanotubes, it is subjected to low-temperature carbonization treatment at 300~400℃ for 1~2 hours. When the electronic conductor precursor is a conductive polymer monomer, it is subjected to ultraviolet curing or low-temperature thermal polymerization treatment.
[0017] More specifically, for graphene oxide or carbon nanotube precursors, low-temperature carbonization at 300-400°C can remove oxygen-containing functional groups on their surface, increase the degree of graphitization, and enhance their electronic conductivity. For conductive polymer monomers, ultraviolet curing or low-temperature thermal polymerization can induce polymerization to form a polymer network with high conductivity. The above post-treatment processes are at low temperatures and will not damage the matrix structure and the nanoporous structure of the coating layer, thus further optimizing the electronic transport performance of the composite coating layer.
[0018] Furthermore, the adhesive is selected from at least one of polyvinylpyrrolidone, polyvinyl alcohol, and polyethylene glycol; The solvent is water, ethanol, or a mixture of both.
[0019] More specifically, the aforementioned binder has good water solubility and adhesion properties, which can effectively enhance the adhesion between the precursor components and the matrix particles, prevent the coating layer from falling off during subsequent processing, and at the same time act as a pore-forming agent to assist in the formation of nanoporous structures during freeze-drying. The use of water, ethanol, or a mixture of the two as solvents avoids the use of toxic and harmful organic solvents, making the process green and environmentally friendly. Moreover, the solvent is easily and completely removed by freeze-drying, leaving no harmful impurities in the final product, making it suitable for large-scale industrial production.
[0020] Furthermore, the inert atmosphere is an Ar atmosphere, and the reducing atmosphere is an Ar / H2 mixed atmosphere.
[0021] More specifically, Ar is used as an inert atmosphere because it is chemically stable and has a low ionization energy. It can form a stable and uniform plasma environment under the action of a radio frequency electric field, effectively isolating impurities such as oxygen and moisture in the air. Ar / H2 mixed atmosphere is used as a reducing atmosphere. On the basis of inert protection, a weak reducing environment is introduced, which can further suppress the oxidation reaction on the material surface and promote the reduction process of electronic conductor precursors such as graphene oxide.
[0022] Furthermore, the amount of fast ion conductor precursor used is 0.5 to 5 wt% of the mass of the single-crystal lithium nickel cobalt manganese oxide matrix powder, based on the final generated fast ion conductor; the amount of electronic conductor precursor used is 0.1 to 2 wt% of the mass of the single-crystal lithium nickel cobalt manganese oxide matrix powder, based on the final generated electronic conductor.
[0023] More specifically, controlling the amount of fast ion conductor to 0.5~5wt% of the matrix mass ensures the formation of a continuous and complete lithium-ion transport network on the matrix surface, effectively reducing interfacial ion transport impedance. It also avoids excessive coating thickness due to excessive fast ion conductor, which would hinder lithium-ion diffusion. At the same time, it reduces the proportion of inactive materials, ensuring high specific capacity of the material. Controlling the amount of electronic conductor to 0.1~2wt% of the matrix mass enables the construction of a continuous and uniform electronic conductivity path on the matrix surface, improving interfacial electronic conductivity. It also prevents particle agglomeration due to excessive electronic conductor and avoids the adverse effects of excessive inactive materials on the material's energy density.
[0024] The second aspect of the present invention provides a high-performance low-temperature lithium battery cathode material, which is prepared by the above-described preparation method; the high-performance low-temperature lithium battery cathode material includes a single-crystal lithium nickel cobalt manganese oxide matrix and a fast ion conductor / electronic conductor composite coating layer with a nanoporous structure coated on the surface of the single-crystal lithium nickel cobalt manganese oxide matrix.
[0025] The cathode material prepared by the above method uses single-crystal lithium nickel cobalt manganese oxide as the matrix, which eliminates the grain boundary impedance of polycrystalline materials and improves the structural stability and lithium ion bulk diffusion rate of the material. The fast ion conductor / electronic conductor composite coating layer with nanoporous structure on the surface of the matrix has abundant lithium ion fast transport channels and continuous electronic conductivity network, which can significantly reduce the interfacial charge transfer impedance at low temperature. Moreover, the coating layer and the matrix form a strong interfacial chemical bond through plasma sintering, which effectively avoids the coating layer falling off during cycling. Thus, the cathode material has high specific capacity, excellent low temperature rate performance and long cycle life.
[0026] The third aspect of this invention provides the application of the above-mentioned high-performance low-temperature lithium battery cathode material in the preparation of low-temperature lithium-ion batteries.
[0027] The application of the aforementioned high-performance low-temperature lithium battery cathode material in the preparation of low-temperature lithium-ion batteries can effectively solve the technical problems of traditional lithium-ion batteries such as significant capacity decay, rate performance deterioration, and poor cycle stability in low-temperature environments. It can significantly improve the discharge capacity, rate performance, and cycle life of batteries in extremely cold environments at -20℃ and below, enabling the batteries to meet the usage needs of electric vehicles, energy storage devices, special equipment, and other fields in high-altitude and cold regions, and expanding the low-temperature application scenarios of lithium-ion batteries.
[0028] The technical solution of this invention can achieve the following technical effects: This invention combines freeze-drying technology with radio frequency plasma-assisted sintering technology, and uses green solvents such as water or ethanol to prepare precursor slurry. First, it rapidly freezes and vacuum freeze-dries to construct a continuous and interconnected nanoporous composite coating layer precursor on the surface of a single-crystal lithium nickel cobalt manganese oxide substrate. Then, it achieves crystallization of fast ion conductors, conversion of electronic conductors, and strong interfacial chemical bonding between the coating layer and the substrate through low-temperature plasma sintering. This avoids the defects of substrate grain growth, structural damage, and coating layer densification caused by traditional high-temperature sintering processes. It also enables the composite coating layer to have abundant lithium-ion fast transport channels and excellent electronic conductivity, significantly reducing the interfacial charge transfer impedance at low temperatures and improving the low-temperature discharge capacity, rate performance, and cycle stability of the cathode material. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 These are the XRD patterns of Example 1 and Comparative Example 2; Figure 2 These are SEM images of Example 1 and Comparative Example 2; Figure 3 The graph shows the charge-discharge cycle performance of the positive electrode materials prepared in Example 1, Comparative Example 1, and Comparative Example 2 assembled into batteries at -20°C and 1C rate. Detailed Implementation
[0031] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0033] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application.
[0034] Example 1:
[0035] This embodiment provides a method for preparing a high-performance low-temperature lithium battery cathode material and the cathode material prepared by this method. The specific steps are as follows: S1 weighs 10g of single-crystal LiNi 0.83 Co 0.11 Mn 0.06 O2 (NCM83A) powder was dispersed in 100 mL of deionized water and ultrasonically dispersed for 30 minutes to obtain a matrix dispersion.
[0036] According to LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) Stoichiometric ratio: Weigh 0.52 g lithium nitrate (LiNO3), 0.65 g aluminum nitrate (Al(NO3)3·9H2O), 3.8 mL tetrabutyl titanate (Ti(OC4H9)4), and 1.2 mL phosphoric acid (H3PO4, 85 wt%), dissolve in 50 mL anhydrous ethanol, and stir until completely dissolved to obtain LATP precursor solution; the amount of LATP generated accounts for approximately 2.5 wt% of the NCM83A matrix mass; The LATP precursor solution was slowly added dropwise to the matrix dispersion while continuously stirring. Then, 25 mL of graphene oxide aqueous dispersion (2 mg / mL) was added, and the mixture was sonicated for 30 minutes to ensure uniform dispersion. The amount of graphene oxide generated was approximately 0.5 wt% of the NCM83A matrix mass. 1 g of polyvinylpyrrolidone (PVP) was added as a binder, and stirring was continued for 2 hours to obtain a homogeneous precursor slurry. S2. The precursor slurry was poured into a petri dish and placed in an ultra-low temperature freezer. It was then rapidly frozen at -80°C for 2 hours to completely freeze the slurry. The frozen sample was then transferred to a freeze dryer and freeze-dried under a vacuum of <10 Pa for 48 hours to obtain a fluffy composite coating precursor powder. S3 The freeze-dried powder was spread evenly in a quartz boat and placed in a radio frequency plasma treatment device. High-purity Ar gas was introduced and the atmosphere pressure was maintained at 50 Pa. The radio frequency power was set to 300 W and the treatment time was 30 minutes. After the treatment was completed, it was naturally cooled to room temperature under the Ar atmosphere. S4 places the plasma-treated powder in a tube furnace and heats it to 350°C at 5°C / min under an Ar atmosphere, holding it at that temperature for 1 hour to partially reduce graphene oxide to reduced graphene oxide (rGO). After natural cooling, it is ground and passed through a 325-mesh sieve to obtain the LATP / rGO composite-coated NCM83A cathode material.
[0037] Example 2:
[0038] The preparation method is the same as in Example 1, except that in step S1, the precursor slurry is prepared by weighing 10g of single-crystal LiNi. 0.83 Co 0.11 Mn 0.06 O2 (NCM83A) powder was dispersed in 100 mL of deionized water and ultrasonically dispersed for 30 minutes to obtain a matrix dispersion.
[0039] According to LLZO (Li7La3Zr2O) 12 According to the stoichiometric ratio, 2.80 g of lithium nitrate (LiNO3), 7.50 g of lanthanum nitrate (La(NO3)3·6H2O), and 4.95 g of zirconium nitrate (Zr(NO3)4·5H2O) were weighed and dissolved in 50 mL of anhydrous ethanol. The solution was stirred until completely dissolved to obtain an LLZO precursor solution. The amount of LLZO formed was approximately 2.5 wt% of the NCM83A matrix.
[0040] The LLZO precursor solution was slowly added dropwise to the matrix dispersion while continuously stirring. Then, 25 mL of graphene oxide aqueous dispersion (2 mg / mL) was added, and the mixture was sonicated for 30 minutes to ensure uniform dispersion. The amount of graphene oxide generated was approximately 0.5 wt% of the NCM83A matrix mass. 1 g of polyvinylpyrrolidone (PVP) was added as a binder, and stirring was continued for 2 hours to obtain a homogeneous precursor slurry.
[0041] Example 3:
[0042] The preparation method is the same as in Example 1, except that in step S1, the precursor slurry is prepared by weighing 10g of single-crystal LiNi. 0.83 Co 0.11 Mn 0.06 O2 (NCM83A) powder was dispersed in 100 mL of deionized water and ultrasonically dispersed for 30 minutes to obtain a matrix dispersion.
[0043] Press LLTO (Li 0.33 La 0.56According to the stoichiometric ratio of TiO3, 0.13 g of lithium nitrate (LiNO3), 1.40 g of lanthanum nitrate (La(NO3)3·6H2O), and 2.4 mL of tetrabutyl titanate (Ti(OC4H9)4) were weighed and dissolved in 50 mL of anhydrous ethanol. The solution was stirred until completely dissolved to obtain an LLTO precursor solution. The amount of LLTO formed was approximately 2.5 wt% of the NCM83A matrix.
[0044] The LLTO precursor solution was slowly added dropwise to the matrix dispersion while continuously stirring. Then, 25 mL of graphene oxide aqueous dispersion (2 mg / mL) was added, and the mixture was sonicated for 30 minutes to ensure uniform dispersion. The amount of graphene oxide generated was approximately 0.5 wt% of the NCM83A matrix mass. 1 g of polyvinylpyrrolidone (PVP) was added as a binder, and stirring was continued for 2 hours to obtain a uniform precursor slurry.
[0045] Example 4:
[0046] The preparation method is the same as in Example 1, except that in step S3, plasma-assisted sintering, the freeze-dried powder is spread evenly in a quartz boat and placed in a radio frequency plasma processing device. High-purity Ar gas is introduced and the atmosphere pressure is maintained at 50 Pa. The radio frequency power is set to 200 W and the processing time is 30 minutes. After processing, it is naturally cooled to room temperature under Ar atmosphere.
[0047] Example 5:
[0048] The preparation method of Example 1 was followed, except that in step S3, plasma-assisted sintering, the freeze-dried powder was spread evenly in a quartz boat and placed in a radio frequency plasma processing device. High-purity Ar gas was introduced and the atmosphere pressure was maintained at 50 Pa. The radio frequency power was set to 400 W and the processing time was 30 minutes. After processing, the powder was naturally cooled to room temperature under the Ar atmosphere.
[0049] Comparative Example 1: Using original single-crystal LiNi 0.83 Co 0.11 Mn 0.06 O2 (NCM83A) powder, without any treatment, was used as a benchmark for performance comparison.
[0050] Comparative Example 2: The preparation method is the same as in Example 1, except that step S3 involves conventional drying and high-temperature sintering. The precursor slurry is stirred and the solvent is evaporated under an 80°C water bath to obtain a dried precursor powder. The dried precursor powder is placed in a tube furnace and heated to 700°C at a rate of 5°C / min under an Ar atmosphere, and held at that temperature for 4 hours. This allows the LATP precursor to be converted into a LATP fast ion conductor and graphene oxide to be reduced to reduced graphene oxide, while simultaneously achieving the bonding between the coating layer and the substrate.
[0051] Material structure and morphology characterization: XRD characterization: The samples of Example 1 and Comparative Example 2 were subjected to phase analysis using an X-ray diffractometer with a scanning range of 10° to 80° and a scanning rate of 5° / min.
[0052] like Figure 1 The test results show that the horizontal axis represents the diffraction angle number in X-ray diffraction, and the vertical axis represents the intensity. The diffraction peak positions and relative intensities of Example 1 and Comparative Example 2 are basically consistent. All characteristic peaks match the standard card PDF#00-056-0293, indicating that the sample has a typical layered oxide structure. This structure belongs to the α-NaFeO2 type structure with space group R-3m. The (006) / (102) and (108) / (110) diffraction peaks in the figure are clearly split, indicating that the layered structure of the material is well ordered and the degree of cation mixing is low. In addition, no obvious impurity phase diffraction peaks were detected in the spectrum, indicating that the sample has high phase purity. The peaks of Example 1 and Comparative Example 2 are sharp and have high intensity, indicating that the material has good crystallinity and that different process conditions have not significantly affected its main crystal structure.
[0053] SEM characterization: The microstructure of Example 1 and Comparative Example 2 was observed in detail using a scanning electron microscope.
[0054] like Figure 2 As shown on the left, the sample particles in Example 1 exhibit a generally polyhedral or quasi-spherical structure with a relatively uniform particle size distribution, clear interfaces between particles, and no obvious severe agglomeration. The particle surfaces are relatively smooth, with a small number of fine particles attached, indicating that they are composed of nanoscale primary grains that are tightly bound, which is conducive to the formation of stable conductive and ion transport channels. In contrast, as... Figure 2 As shown on the right, the particle size of the Comparative Example 2 sample is significantly increased and unevenly distributed, exhibiting an irregular blocky structure. Some areas show obvious particle fusion and sintering phenomena, and the particle surface is abnormally smooth with local flow marks, indicating that there is excessive sintering behavior during the preparation process, which leads to grain growth and structural densification, thereby reducing the specific surface area of the material and aggravating particle agglomeration. In summary, Example 1 has advantages in inhibiting excessive grain growth, improving particle dispersion, and maintaining structural integrity.
[0055] The positive electrode materials prepared in the above examples and comparative examples were mixed with conductive agent Super P and binder PVDF at a mass ratio of 8:1:1, respectively, and N-methylpyrrolidone (NMP) was used as a solvent to form a slurry. The slurry was uniformly coated onto aluminum foil, and then vacuum dried and rolled to form a positive electrode sheet. Using a lithium metal sheet as the counter electrode, Celgard 2400 as the separator, and 1 mol / L LiPF6 (solvent:EC:EMC = 3:7 volume ratio, with the addition of 0.05 mol / L LiNO3, 0.2 mol / L LiFSI, and 5 wt% FEC) as the electrolyte, CR2032 coin cell half-cells were assembled in an argon glove box, and then the following tests were performed: Test conditions: Voltage range: 2.8~4.3V (vs. Li + / Li), ambient temperature test temperature: 25℃±1℃, low temperature test temperature: -20℃±1℃, rate test: charge and discharge 5 times each at 0.1C, 1C and 5C rates; cycle test: charge and discharge 100 times at 1C rate.
[0056] The test results are shown in Tables 1 and 2: Table 1. Rate discharge specific capacity (mAh / g) of the Examples and Comparative Examples at 25°C
[0057] Table 2. Rate discharge specific capacity (mAh / g) of the examples and comparative examples at -20℃
[0058] Figure 3This graph compares the cycling performance of Example 1 and Comparative Example 2 at -20℃ and 1C rate. The horizontal axis represents the number of cycles, the left vertical axis represents capacity, and the right vertical axis represents coulombic efficiency. As can be seen from the graph, the LATP / rGO composite-coated NCM83A cathode material prepared in Example 1 exhibits excellent cycling stability at -20℃. After 100 charge-discharge cycles, its capacity retention rate is significantly higher than that of Comparative Example 1 and Comparative Example 2. The first-cycle discharge specific capacity of Example 1 is approximately 135.72 mAh / g, and it still maintains approximately 124.56 mAh / g after 100 cycles, with a capacity retention rate of 91.9%. The first-cycle discharge specific capacity of Comparative Example 2 is approximately 93.71 mAh / g, which decreases to approximately 69.65 mAh / g after 45 cycles, with a capacity retention rate of only 73.63%. The first-cycle discharge specific capacity of Comparative Example 1 is approximately 79.56 mAh / g, which decreases to approximately 54.69 mAh / g after 36 cycles, with a capacity retention rate of only 68.35%. The results fully demonstrate that the strong interfacial bonding formed by the nanoporous structure constructed by freeze-drying and plasma low-temperature assisted sintering in this invention can effectively improve the cycling stability of materials in low-temperature environments, and the effect is significantly better than that of traditional high-temperature sintering processes.
[0059] From Table 1, Table 2 and Figure 3 Data shows that, at room temperature and rate performance: Example 1 achieved a discharge specific capacity of 209.82 mAh / g at 0.1C, 188.76 mAh / g at 1C, and maintained 165.43 mAh / g at a high rate of 5C, with a capacity retention rate of 78.9% from 0.1C. Compared with Comparative Example 1 (uncoated, only 120.25 mAh / g at 5C), the 5C discharge specific capacity increased by approximately 37.6%, demonstrating that the porous composite coating layer constructed in this invention can effectively improve the electron and ion transport dynamics of the material and significantly enhance rate performance.
[0060] Low-temperature rate performance: Example 1 achieved a discharge specific capacity of 162.43 mAh / g at -20℃ and 0.1C, 135.72 mAh / g at 1C, and maintained 98.65 mAh / g at 5C, with a capacity retention rate of 60.7% from 0.1C at 5C. Compared with Comparative Example 1 (only 28.39 mAh / g at -20℃ and 5C), the low-temperature discharge specific capacity at 5C increased by approximately 247%; compared with Comparative Example 2 (52.24 mAh / g at -20℃ and 5C), the low-temperature discharge specific capacity at 5C increased by approximately 88.8%. The above data indicate that the nanoporous composite coating layer of the present invention can still provide abundant fast transport channels for lithium ions under low-temperature conditions, effectively reducing interfacial charge transfer impedance, thereby significantly improving the low-temperature rate performance of the material.
[0061] Comparison of different fast ion conductors: Examples 1-3 respectively used LATP, LLZO, and LLTO fast ion conductors to coat rGO, and all achieved significant performance improvements. Among them, Example 1 (LATP system) had the best overall performance, followed by Example 2 (LLZO system), and Example 3 (LLTO system) was third. All three fast ion conductors can effectively improve the low-temperature performance of the material, indicating that the process of the present invention has good universality for different types of fast ion conductors.
[0062] The comparative results of Examples 1 (300W), 4 (200W), and 5 (400W) show that the material prepared with a plasma power of 300W exhibits the best rate performance at both room temperature and low temperature. Too low a power may result in insufficient crystallization of the coating layer and weak interfacial bonding; too high a power may cause slight damage to the substrate surface, affecting electrochemical performance. Therefore, the preferred radio frequency power is 300W.
[0063] Process Comparison: The performance of Example 1 is significantly superior to that of Comparative Example 2 (traditional high-temperature sintering coating). At -20℃ and 5C, the discharge specific capacity of Example 1 (98.65 mAh / g) is 88.8% higher than that of Comparative Example 2 (52.24 mAh / g). Regarding cycle stability at -20℃ and 1C, Example 1 maintains a capacity retention rate of 91.9% after 100 cycles, while Comparative Example 2's capacity retention rate drops to 73.63% after only 45 cycles, and the uncoated Comparative Example 1 drops to 68.35% after only 36 cycles. These results fully demonstrate that the process of constructing a nanoporous structure using freeze-drying combined with plasma-assisted low-temperature sintering to form a strong interfacial bond has significant advantages in improving the low-temperature electrochemical performance of materials, and its effect is far superior to the traditional high-temperature sintering coating process.
[0064] Although this application has been described in conjunction with specific features and embodiments, it is obvious that various modifications and combinations can be made thereto without departing from the spirit and scope of this application. Accordingly, this specification and drawings are merely exemplary illustrations of the application as defined herein, and are to be considered as covering any and all modifications, variations, combinations, or equivalents within the scope of this application. Clearly, those skilled in the art can make various alterations and modifications to this application without departing from its scope. Thus, if such modifications and modifications fall within the scope of this application and its equivalents, this application intends to include such modifications and modifications.
Claims
1. A method for preparing a high-performance low-temperature lithium battery cathode material, characterized in that, The method includes: S1 disperses single-crystal lithium nickel cobalt manganese oxide matrix powder, fast ion conductor precursor, electronic conductor precursor and binder in solvent, mixes them evenly to obtain precursor slurry; S2 rapidly freezes the precursor slurry at a temperature of -50℃ to -196℃, and then freeze-dries it under vacuum for 24 to 48 hours to obtain a composite coating layer precursor with a nanoporous structure. S3 The composite coating precursor is placed in a plasma treatment device and assisted in sintering under an inert or reducing atmosphere using radio frequency plasma. The radio frequency power is 200~500W, the treatment time is 10~60 minutes, and the atmosphere pressure is 10~100Pa. S4 cools, grinds, and sieves the product after assisted sintering to obtain the high-performance low-temperature lithium battery cathode material.
2. The preparation method according to claim 1, characterized in that, The chemical formula of the single-crystal lithium nickel cobalt manganese oxide matrix powder is LiNi x Co y Mn 1-x-y O2, where 0.3≤x≤0.9, 0.05≤y≤0.
3.
3. The preparation method according to claim 1, characterized in that, The fast ion conductor precursor is selected from salts or alkoxides containing at least two elements selected from Li, Al, Ti, La, Zr, Ge, and P, and is used to form at least one of LATP, LLZO, LLTO, and LAGP fast ion conductors.
4. The preparation method according to claim 1, characterized in that, The electronic conductor precursor is selected from at least one of graphene oxide, carbon nanotubes, MXene nanosheets, and conductive polymer monomers; The conductive polymer monomer includes at least one of aniline, pyrrole, and thiophene.
5. The preparation method according to claim 4, characterized in that, Between S3 and S4, there is also a post-processing step: When the electronic conductor precursor is graphene oxide or carbon nanotubes, it is subjected to low-temperature carbonization treatment at 300~400℃ for 1~2 hours. When the electronic conductor precursor is a conductive polymer monomer, it is subjected to ultraviolet curing or low-temperature thermal polymerization treatment.
6. The preparation method according to claim 1, characterized in that, The adhesive is selected from at least one of polyvinylpyrrolidone, polyvinyl alcohol, and polyethylene glycol; The solvent is water, ethanol, or a mixture of both.
7. The preparation method according to claim 1, characterized in that, The inert atmosphere is an Ar atmosphere, and the reducing atmosphere is an Ar / H2 mixed atmosphere.
8. The preparation method according to claim 1, characterized in that, The amount of the fast ion conductor precursor, based on the final fast ion conductor, accounts for 0.5 to 5 wt% of the mass of the single-crystal lithium nickel cobalt manganese oxide matrix powder; the amount of the electronic conductor precursor, based on the final electronic conductor, accounts for 0.1 to 2 wt% of the mass of the single-crystal lithium nickel cobalt manganese oxide matrix powder.
9. A high-performance low-temperature lithium battery cathode material, characterized in that, The high-performance low-temperature lithium battery cathode material is prepared by any one of claims 1 to 8; the high-performance low-temperature lithium battery cathode material includes a single-crystal lithium nickel cobalt manganese oxide matrix and a fast ion conductor / electron conductor composite coating layer with a nanoporous structure coated on the surface of the single-crystal lithium nickel cobalt manganese oxide matrix.
10. The application of the high-performance low-temperature lithium battery cathode material according to claim 9 in the preparation of low-temperature lithium-ion batteries.